Threat of Abstention as a Form of Community Political Criticism Case Study in Rather Village, Sebangki District, Landak Regency: Studi Kasus di Desa Agak Kecamatan Sebangki Kabupaten Landak - Nge, Herri Junius (Indonesian Journal of Advanced Research, 2024)
The phenomenon of the threat of abstention is an indication that there is public disappointment with the government. Even though abstaining from voting is a citizen's right, the existence of a collective movement not to vote is a warning to the government regarding the quality of democratic life. The aim of this research is to analyze the emergence of the threat of abstention as a form of political criticism in the community in Punyanget Hamlet, Agak Village, Sebangki District, Landak Regency. The method used to achieve the research objectives is qualitative, with a case study type of research.. The results of the research show that the threat of abstention from the residents of Punyanget Hamlet as a form of social movement is caused by the alienation of residents who are lagging behind in terms of development compared to other hamlets. This has raised the collective awareness of the hamlet residents, involving community leaders, to carry out action in the form of an abstention movement in the 2024 elections. Community social movements as a form of collective action are able to provide reactions to related parties, because the actions taken take advantage of the political moment related to the event. general elections. Even though this movement tends to be incidental and not designed with a clear movement structure, it is able to build the collective spirit of citizens to carry out protests with the threat of abstaining from voting in the 2024 elections, by using social media as a platform for the movement to gain public support.